Holy Roman Empira of Severius of Monzambano - Netto de Andrade e Silva Sahd, Luiz Felipe (Sofia, 2023)
The examination of Pufendorf's De Statu Imperii Germanici shows that he was strongly interested in the question of sovereignty, and that the complex reality of the Holy Roman Empire demanded a completely new approach to the question of where sovereignty within the Empire lay. I argue that the type of state that Pufendorf had in mind was the composite state represented by the Holy Roman Empire, consisting of many different communities divided by religion but sharing the same sovereign, the Catholic Holy Roman Emperor.
Keywords: empire; composite state; sovereignty; war and peace; moral person